2002
DOI: 10.1007/s005950200048
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Regional Chemotherapy Using CDDP-Loaded Microspheres for Esophageal Cancer

Abstract: These results demonstrate that a high dose of CDDP can be administered with less systemic side effects by means of encapsulation in the microspheres, and that the administration of CDDP-MS into the mediastinum is more effective for delivering CDDP to the paratracheal lymph nodes. As a regional chemotherapy after esophageal cancer operation, the injection of CDDP-MS into the mediastinum for targeting of the lymph nodes thus promises to be an effective treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Despite its success, cisplatin has several drawbacks including many side effects (e.g., nephrotoxicity, neurotoxicity, and emetogensis) and limited solubility in aqueous solution (typical dose 100 mg/day for up to 5 consecutive days) 2. Therefore, various drug delivery devices including lipsomes,5, 6 micelles,7–9 nanoparticles,10 carbon nanohorns,11, 12 microparticles,13–19 and composite microparticles (PLA/PLGA)20, 21 have been developed to minimize the side effects and to improve the efficacy of its therapy. In addition, Burger et al and Ramachandran et al reported cisplatin nanolipsomes and lipid‐coated aggregates of cisplatin, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its success, cisplatin has several drawbacks including many side effects (e.g., nephrotoxicity, neurotoxicity, and emetogensis) and limited solubility in aqueous solution (typical dose 100 mg/day for up to 5 consecutive days) 2. Therefore, various drug delivery devices including lipsomes,5, 6 micelles,7–9 nanoparticles,10 carbon nanohorns,11, 12 microparticles,13–19 and composite microparticles (PLA/PLGA)20, 21 have been developed to minimize the side effects and to improve the efficacy of its therapy. In addition, Burger et al and Ramachandran et al reported cisplatin nanolipsomes and lipid‐coated aggregates of cisplatin, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The colloidal particles administered interstitially are mainly taken up by the regional lymphatic system and accumulate to varying degrees in the lymph nodes in our previous study [14]. This unique selective biodistribution led to the development of lymphatic targeting drug delivery systems utilizing colloidal materials as drug carriers, such as liposomes [15], activated carbon particles [16], emulsions [17], lipids [18], and various polymeric particulates [19].…”
Section: Introductionmentioning
confidence: 98%
“…A consistent finding in these studies is that the colloidal particles administered interstitially are mainly taken up by the regional lymphatic system and accumulate to varying degrees in the lymph nodes. This unique selective biodistribution led to the development of lymphatic targeting drug delivery systems utilizing colloidal materials as drug carriers, such as liposomes [8][9][10], activated carbon particles [11,12], emulsions [13,14], lipids [15] and various polymeric particulates [16,17]. However, lymphatic distribution of particles of different materials and sizes following intrapleural administration has not been investigated.…”
Section: Introductionmentioning
confidence: 99%